Toward an Integrative Model of Strategic International Human Resource Management - Taylor, Sully; Beechler, Schon; Napier, Nancy K. (Academy of Management Review, 1996)
This article builds on previous work in international human resource management by drawing on concepts from the resource-based view of the firm and resource dependence to develop a theoretical model of the determinants at strategic international human resource management (SIHRM) systems in multinational corporations. The article then offers propositions concerning the relationships between a number of key determinants and the multinational corporation's overall SIHRM approach, the design of a particular affiliate's HRM system, and the HRM system for critical groups of employees within the affiliate.